2019
DOI: 10.21608/zvjz.2019.14914.1061
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Ginger Aqueous Extract against Imidacloprid-Induced Neurotoxicity in Rats

Abstract: The current study was aimed to investigate neurotoxic impact of imidacloprid in rats and the potential modulatory role of Zingiber officinale Roscoe aqueous extract against such effects. Sixty male albino rats were randomly assigned into six groups (n = 10) as following: G1 is (-ve) control group (0.1 ml of distilled water for 90 days). G2 is (+ve) control group (1ml of aqueous extract of ginger (GAE) for 90 days). G3 group was administered with 0.1 ml of Imidacloprid (IMI) for 90 days. G4 group was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(38 reference statements)
2
1
0
Order By: Relevance
“…However, GABA levels induced by Topamax® highly exceeded that induced by ginger oil. In Consistent with our results, Farag et al [20] revealed that ginger supplementation has been associated with an increased GABA concentration in the hippocampus as well as cerebral cortex of senile female rats. GABA levels elicited in the brain of mice treated with Topamax® and ginger oil were found to be lower than in Topamax® treated animals in the current investigation.…”
Section: Discussionsupporting
confidence: 93%
“…However, GABA levels induced by Topamax® highly exceeded that induced by ginger oil. In Consistent with our results, Farag et al [20] revealed that ginger supplementation has been associated with an increased GABA concentration in the hippocampus as well as cerebral cortex of senile female rats. GABA levels elicited in the brain of mice treated with Topamax® and ginger oil were found to be lower than in Topamax® treated animals in the current investigation.…”
Section: Discussionsupporting
confidence: 93%
“…The spleen is a peripheral lymphoid organ that plays a crucial role in the body's innate and adaptive immune responses against systemically acquired antigens [133,134].To the best of our knowledge, this is the first study that reported that IMI-induced up-regulated the expression level of the TLR-4 gene in the spleen of IMI-exposed broilers. Similar findings were obtained by Farag, et al [135], who found that the Toll-like receptor 2 (TLR2) gene was up-regulated in the brains of rats after IMI exposure, while TLR2 had a strong immunopositive response in the brains of IMI-treated rats. Toll-like receptor is activated by molecules generated from pathogens, which causes the production of inflammatory mediators including TNF-α [136].…”
Section: Discussionsupporting
confidence: 88%
“… ). The increase of TLR2 in this study is consistent with the results of a previous report in which imidacloprid was administered chronically [ 7 ]. The cerebral microglia are responsible for immune function that induces inflammation via TLR2 expression [ 24 ].…”
supporting
confidence: 92%